Historical Dictionary of Tajikistan - Abdullaev, Kamoludin (Historical dictionaries of Asia, Oceania, and the Middle East., 2018)
This third edition of Historical Dictionary of Tajikistan contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 800 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture.